"Outcomes of arteriovenous fistulae cannulation in the first 6 weeks of use: A retrospective multicenter observational study". Issue 5 (September 2021) - Hill, Kathleen; Xu, Qunyan; Jaensch, Ashleigh; Esterman, Adrian; Le Leu, Richard; Childs, Jessie; Juneja, Rajiv; Jesudason, Shilpanjali
Background: Arteriovenous fistula (AVF) management for haemodialysis (HD) is one of the most challenging aspects of clinical care. A successful cannulation outcome when an AVF or arteriovenous graft (AVG) is used for the first time can be influenced by many factors, including access maturity, staff skill, and patient factors. This study examined AVF/AVG outcomes at initiation of HD across two major metropolitan public hospitals. Methods: Electronic medical records were reviewed to collect data retrospectively for a cohort of all newly commencing ESRD HD starts during 2018 to identify cannulation outcomes in the first 6 weeks. Results: Of the 117 patients included, AVG use was low (5%). Twenty-four percent of patients required a surgical intervention to salvage a poorly functioning AVF prior to commencing HD. About 32.5% of the cohort had an uneventful start with all successful cannulations. For the remainder of the cohort the number of treatments with unsuccessful cannulation ranged from 1 to 4 or more. About 36% required a surgical intervention for a poorly functioning AVF after commencing HD. Commencing HD with a CVC is associated with a lower likelihood of subsequent successful cannulation ( p < 0.001). Conclusion: Even in experienced centres, a subset of patients experienced complicated cannulation in the first 6 weeks of HD. Several areas of improvement could be considered for these patients; timely referral for access creation, post-operative surveillance to ensure AVF maturation inclusive of duplex ultrasonography, gentle induction using small gauge needles and low blood flows, and consideration of a single needle HD initiation pathway.